Customer Relations Management in Fourth Party Logistics and its Influence on Performance of Food and Beverage Manufacturing Firms in Kenya - Jepchumba, Naomy Jepchumba; Ngugi, Patrick Karanja; Shale, Noor Ismail; Odhiambo, Romanus Odhiambo (International Journal of Supply Chain and Logistics, 2022)
Purpose: The aim of this study was to establish role played by customer relations management as an aspect of fourth party logistics on performance of food and beverage manufacturing companies in Kenya. The study was anchored on the partnerships theory that upholds the need for bringing the customers closer in order to understand and meet their needs. Methodology: This research study adopted a descriptive and cross-sectional research designs. The designs were preferred since they allowed both in-depth study of the subject and comparison of the relationship between variables. Data was collected using self-administered questionnaires. The data collected was analysed by use of descriptive and inferential statistics. A regression model was used to show the relationship between the dependent variable and the independent variable. Findings: The findings from the study revealed that customer relations management as one of the core components of fourth party logistics play an integral role in enhancing the performance of food and beverage processing firms. The study concluded that fourth party logistics through customer relations management is critical in enhancing the performance of food and beverage processing firms in Kenya. Unique contribution to theory, practice and policy: The study recommended that the management of food and beverage processing firms ought to embrace fourth party logistics services by bringing customers on board in order to gain performance